Correlation of Organizational Culture with Company Innovation - Miftahul Rahmat Rauf; Haedar Akib; Muhammad Rizal (Universitas Negeri Makassar, 2020)
Copyright © 2020 Universitas Negeri Makassar. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/) Organizational Culture is an important component in organization. This research discussed the correlation of organizational culture with company innovation in Perum Bulog Sulselbar Regional Divisions. This type of research is a descriptive research using a quantitative study design. Data collected techniques are carried out through observation, questionnaires and documentation. In this study, researchers tried to ascertain whether organizational culture has a relationship with company innovation. This research using a survey method. The data was collected by a questionnaire and analyzed using a statistical formula, with Spearman Rank Correlation which is calculated using SPSS. Based on data processing for the organizational culture variable, it was obtained a value of 82 percent, so it concluded that the organizational culture, was in the very good category. For the company's innovation variable obtained a value of 86 percent, so it concluded that the innovation is in the very good category. The results of this study are that there is a relationship between organizational culture with company innovation, with a high correlation coefficient score up to = 0,705, So it can be concluded that organizational culture is correlated with a high level of correlation with company innovation at the general company Bulog, the Regional Division of South Sulawesi in Makassar.